Peran Fundamental Roh Kudus Dalam Pembentukan Psikologi Manusia Dari Perspektif Teologis dan Psikospiritual - Avlorina, Mey (Sekolah Tinggi Teologi Injili Indonesia Palu, 2025)
This article explores the fundamental role of the Holy Spirit in shaping human psychology from a theological and psycho-spiritual perspective. The study aims to understand how the work of the Holy Spirit influences the development of an individual’s mental, emotional, and moral life. The method employed is a literature review of biblical texts alongside contemporary theological and psychological sources. The findings indicate that the Holy Spirit plays an active role in inner regeneration, the renewal of the mind, and the cultivation of the fruit of the Spirit—elements that align closely with the framework of positive psychology. In conclusion, the Holy Spirit is a transformative agent in shaping human psychological wholeness in accordance with the will of God.